Uma análise histórica da concepção de educação de Constantin Stanislavski: um diálogo entre o teatro e a pedagogia - Souza, Jacqueline Ellen de (2022)
This work has as a purpose the investigation of the concept of education in the works that compose the trilogy: An actor prepares (1989); Building a Character (1989) and Creating a Role (1989) of the System of actor formation created by the dramatist Constantin Stanislavski. When researching about his System in research engines e journal directories, it was observed that the educational issue in Stanislavski's works finds little resonance in researches in the education area and, it was also observed, researches on the author’s method that doesn’t address the trilogy in its integrity and its theoretic-methodological foundation. In this sense, the following work opted by investigating the System in relation to his historical context, its form of creation and exposition, that is, how it comes to public knowledge, as well the organization of his ideas about the actor formation, the matters of interpretation and representation regarding the public, the social function of the theater and his political perspectives of social conservation or transformation. Therefore, by using bibliographic research, taking attention to the political and historical context, we sought to verify the process of creation and exposition of the pedagogical categories in the books. Overall, Stanislavski's books sought to answer the problems existing in that context, in a way to offer solutions to the challenges of pre- and post-revolution Russia. The process of writing and publication were permeated by interruptions and difficulties, deserving of a highlight is the hardships around the translation of the books and its commercialization in the editorial market in the United States. Although Stanislavski wasn't worried in creating a tract about school education, his work has many pedagogical categories as: concentration capacity, observation, discipline, plasticity, sense of objective and among other categories. Lastly, it is marked that the author's thought shows a concern about the process of transformation of the Russian social basis and his formative perspective, the actor and/or the art should have a commitment with collective society. In conclusion, the System formulated by Stanislavski goes way beyond the theatrical formation, complementing the school formation, keeping itself current, furthermore in today's society